Elasticity of Orthoenstatite at High Pressure and Temperature: Implications for the Origin of Low VP/VS Zones in the Mantle Wedge. Issue 2 (24th January 2018) - Qian, Wangsheng; Wang, Wenzhong; Zou, Fan; Wu, Zhongqing
Abstract: Orthopyroxene (opx) is an important mineral in petrologic models for the upper mantle. Its elastic properties are fundamental for understanding the chemical composition and geodynamics of the upper mantle. Here we calculate the elastic properties of orthoenstatite (MgSiO3 ), the Mg end‐member orthopyroxene under upper mantle pressure and temperature conditions using first principle calculations with local density approximation. Bulk and shear moduli increase nonlinearly with pressure at mantle temperatures, but the shear modulus and V S show very weak pressure dependence in comparison with V P . Compared to other major minerals in the upper mantle, orthoenstatite has the lowest compressional velocities ( V P ), shear velocities ( V S ), and V P / V S ratio down to the depth of approximately 300 km. The enrichment of opx in the upper mantle can cause the unusually low V P / V S observed in the mantle wedge. Key Points: The elastic properties of orthoenstatite are determined at mantle pressure and temperature conditions using first principle calculations Orthoenstatite has a lower V P, V S, and V P / V S ratio in the uppermost mantle than olivine and pyrope The enrichment of orthopyroxene can cause the unusually low V P / V S in the mantle wedge